(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Organizations are using digital power for growing the business. The industries and business are highly focusing now one-marketing advertisements rather than other advertisement tools. Due to the digital revolution, people are more and more connected to each other, which make access to information easier. In present scenario number of mobile users is increasing day by day and after 2015 maximum number of people use digital platform. So it is easy for the organizations to reach the potential customers for promoting the product and services. This research papers how that people are aware with digital marketing and both male & female use digital platform and factors like easy to use, convenience, quality of the product play important role for buying a product through digital platform. This study is performed in a particular geographical area and this may be considered as a limitation to judge the purchase decisions of all customers of various regions. The study was carried out through a survey among 50 respondents.